POLICY-RELATED FACTORS AND TEACHERS' QUALIFICATIONS AS DETERMINANTS OF TEACHING OF ARABIC LANGUAGE - Taofeeq Olamilekan Sanusi; Ibrahim Solahudeen Owoyale-AbdulGaniy; Jamiu Abdur-Rafiu (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
The study examined policy-related factors and teachers' qualifications as determinants teaching of the Arabic language in secondary schools in Kwara State. A descriptive survey research design was adopted. The population of Kwara South was 23,458, and a sample of 379 students was collected using Kredjcie and Morgan's table. Multistage sampling procedures were adopted including purposive sampling to select three Local Government Areas (LGAs) and simple random sampling to select 30 public schools, 10 from each of the three LGAs. The researcher’s instrument, titled Adapted Policy Related Factors and Teachers' Qualifications as Determinants of Teaching Arabic Language Questionnaire (PRFTQTALQ) was used for data collection. The study found no significant difference in the perception of Arabic language teachers regarding policy-related factors and their qualifications as determinants of teaching Arabic in senior secondary schools in Kwara State. Therefore, the study concluded that there is no significant difference in teachers' perception of policy-related factors affecting the teaching of Arabic in senior secondary schools in Kwara State. The study found no significant difference in teachers' perceptions of Arabic teachers' qualifications determining their teaching of Arabic in senior secondary schools in Kwara State. It recommended amending the National Curriculum and Government policy to make Arabic a compulsory subject in Kwara State's senior secondary schools and awarding in-service training and scholarships for further studies to Arabic language teachers.